Biocultural memory of reciprocity: the Mapuche trafkintu as social-ecological relationships of care and vindication - Salazar, Gonzalo; Reyes, Magdalena; Kaulen-Luks, Santiago; Barrera, Maria Guadalupe; Burgos, Alison; Ibarra, Jose Tomas (My University, 2025)
Reconsidering the relationship between humans and more-than-human beings amid global crises has brought reciprocity practices between people and biodiversity to the forefront. We examine social-ecological reciprocity practices within Indigenous territories and their direct connection to biocultural memory. Specifically, we explore the Mapuche practice of trafkintu in the Andean zone of Wallmapu, La Araucanía region of southern Chile. Using a mixed-methods framework, from a relational perspective, we integrate spatial analysis of a seed exchange network involving 80 local farmers, with an ethnographic and collaborative phase with 12 Mapuche women-who are part of this network-over three years. We found that social-ecological reciprocity practices-like those in the trafkintu-are constitutive of a biocultural memory. This biocultural memory has been vital for sustaining and transforming social-ecological reciprocity practices amid colonial and neo-colonial pressures. We term this recursion the "memory of reciprocity." This provides key insights into how reciprocity manifests as a quality of complex social-ecological relationships, marked by mutual care among people, seeds, and other more-than-human beings. It also helps us understand how, amid the colonialism and dispossession endured by Indigenous peoples for centuries, reciprocity has been essential to survival and vindication.
Keywords: biocultural memory; reciprocity; indigenous relations; social-ecological systems; relational methodology